Presenting characteristics and processing times for culturally and linguistically diverse (CALD) patients with chest pain in an emergency department: Time, Ethnicity, and Delay (TED) Study II. (1st October 2016) - Wechkunanukul, Kannikar; Grantham, Hugh; Teubner, David; Hyun, Karice K.; Clark, Robyn A.
Abstract: Background: To date there has been limited published data presenting the characteristics and timeliness of the management in an Emergency Department (ED) for culturally and linguistically diverse (CALD) patients presenting with chest pain. This study aimed to describe the presenting characteristics and processing times for CALD patients with chest pain compared to the Australian-born population, and current guidelines. Methods: This study was a cross sectional analysis of a cohort of patients who presented with chest pain to the metropolitan hospital between 1 July 2012 and 30 June 2014. Results: Of the total study population (n = 6640), 1241 (18.7%) were CALD and 5399 (81.3%) were Australian-born. CALD patients were significantly older than Australian-born patients (mean age 62 vs 56 years, p < 0.001). There were no differences in the proportion of patients who had central chest pain (74.9% vs 75.7%, p = 0.526); ambulance utilisation (41.7% vs 41.1%, p = 0.697); and time to initial treatment in ED (21 vs 22 min, p = 0.375). However, CALD patients spent a significantly longer total time in ED (5.4 vs 4.3 h, p < 0.001). There was no difference in guideline concordance between the two groups with low rates of 12.5% vs 13%, p = 0.556. Nonetheless, CALD patients were 22% (95% CI, 0.65, 0.95, p = 0.015) less likely to receive the guideline management for chest pain. Conclusions: The initial emergency care was equally provided to all patients in the context of a low rate of concordance with three chest pain related standards from the two guidelines. Nonetheless, CALD patients spent a longer time in ED compared to the Australian-born group.